The Application of the Philosophical Thinking of “Three” From I Ching to Medical Education - Du, Yingjie; Zhang, Xinqing; Zhang, Jinjing; Wang, Guyan (Frontiers in Medicine, 2021)
Since ancient times, the Chinese have had a special feeling about “Three”. Chinese philosophy originates from the I Ching, and the philosophical concept of “Three” is the core of the I Ching. The philosophical thinking about “Three” is a complete dialectical thinking method that is consistent with the Western philosophical concept of “One Dividing into Three”. This paper analyzes the phenomenon of “Three”, examines the culture of “Three”, discusses the charm of “Three”, and applies the philosophical thinking of “Three” to clinical medical education, including the study and application of new technology and new medicine, the shared decision-making between doctors and patients, and the integration of medical humanities and medical science, which is of great significance.